Improved Cut-off Frequency for Cylindrical Gate TFET Using Source Delta Doping. (2016) - Dash, Sidhartha; Sahoo, Girija Shankar; Mishra, Guru Prasad
Abstract: The radio-frequency (RF) performance of delta-doped cylindrical gate Tunnel FET (DCG-TFET) has been investigated and compared with conventional CG-TFET in terms of total gate capacitance, transconductance and cut-off frequency. Because of the higher transconductance due to insertion of delta-doping sheet in the source region, the DCG-TFET model exhibit higher cut-off frequency and smaller intrinsic delay. The impact of variation in gate oxide thickness and silicon pillar diameter on cut-off frequency has also been discussed for the model. The achievement of high cut-off frequency enables the model to be part of a solution in high frequency application. However the RF parameters have been extracted using 2D TCAD device simulator from Synopsis.